2010
DOI: 10.1002/bmc.1565
|View full text |Cite
|
Sign up to set email alerts
|

An LC‐MS/MS method for simultaneous determination of vincristine and verapamil in rat plasma after oral administration of a dual agent formulation

Abstract: A rapid and sensitive method for simultaneous determination of vincristine and verapamil in rat plasma was first developed and validated, using high-performance liquid chromatography-tandem mass spectrometry (LC-MS/MS) in multiple reaction monitoring (MRM) mode via electrospray ionization (ESI). The method, which required a small sample volume (25 µL) of plasma, was linear in the concentration range of 0.5-500 ng/mL for vincristine and 0.1-100.0 ng/mL for verapamil. Finally, the method was successfully employe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…The presence of doubly charged ions was ensured thanks to the ion trap working in high resolution, but [TAX + 2H] 2+ fragments ion currents were lost during chromatographic runs, probably owing to scarce signal intensities. The collision‐induced fragmentation processes of CDs have been studied by other research groups and reported in many articles (Sottani et al , ; Barbieri et al , ; Ling et al , ; Sun et al , ; Fabrizi et al , ). For this reason, we will not add any more considerations to this subject.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of doubly charged ions was ensured thanks to the ion trap working in high resolution, but [TAX + 2H] 2+ fragments ion currents were lost during chromatographic runs, probably owing to scarce signal intensities. The collision‐induced fragmentation processes of CDs have been studied by other research groups and reported in many articles (Sottani et al , ; Barbieri et al , ; Ling et al , ; Sun et al , ; Fabrizi et al , ). For this reason, we will not add any more considerations to this subject.…”
Section: Resultsmentioning
confidence: 99%
“…[13] performed an analysis of vincristine using only 5 μL of blood plasma, which is less than what was used in the current study, however, the overall volume of whole blood collected was 30 μL, which is three times greater than what was achieved using VAMS devices. The chromatographic run time (6.0 min) lay approximately in the middle in terms of throughput of vincristine, with studies reporting gradients between 2 and 5 min [13, 25, 27]. Conversely, analysis of tariquidar was faster in this study compared to other available methods [30, 33].…”
Section: Discussionmentioning
confidence: 81%
“…Validation parameters achieved in this study are comparable to currently available methods for the quantification of vincristine and tariquidar analytes. Most published studies utilize LC-MS/MS instrumentation for quantification of vincristine [13,[23][24][25][26][27][28][29]and tariquidar [30] over HPLC with ultraviolet detection [31][32][33] given its superior sensitivity. To date, this study has achieved the lowest collected mouse whole blood volume for accurate quantification of both analytes.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of vinca alkaloids has been carried out on plant extracts, [398][399][400][401][402][403] pharmaceutical formulations, 316,404 biological samples 358,359,[405][406][407][408][409][410][411][412][413][414][415][416][417][418][419][420]421 and environmental samples. 18,19,134,307,422 Vinca alcaloid extraction from plants was generally performed by ultrasound in acid media followed by LLE.…”
Section: Antitubulin Agentsmentioning
confidence: 99%